The effeects of incerasing GleptoForte dosage on newborn piglet blood and growth parameters - Wecker, Haley K.; Williams, Hayden E.; Jones, Cassandra K.; DeRouchey, Joel M.; Tokach, Michael D.; Woodworth, Jason C.; Goodband, Robert D.; Dritz, Steven S.; Holtcamp, A. (My University, 2017)
The objective of this experiment was to determine the effect of increasing Gleptoforte dosage on newborn piglet blood and growth parameters. A total of 336 suckling pigs (DNA 241 x 600, initially 3.83 0.114 lb BW) from 28 sows were used in a 21-d farrowing study. Piglets were weighed at d3 and 6 barrows and 6 gilts per litter were allotted to treatment within litter for a total of 56 piglets per treatment in a completely randomized design. Treatments consisted of a negative control and increasing levels of iron from Gleptoforte 50, 100, 150, 200, or 200mg plus a 100mg booster at d11. Lactation feed contained 110mg/kg added iron from ferrous sulfate. Piglets were weighed at d3, d11, and d21 to calculate ADG. On d3, d11, and d21 barrows were utilized for blood collection via jugular venipuncture. After blood collection, Hemoglobin (Hgb), Hematocrit (Hct), Serum Fe, and Total Iron Binding Capacity (TIBC) were measured. Piglet d11 BW increased (quadratic, P=0.018) with increasing dosage of Gleptoforte. From d0 to d21, ADG and final BW improved (quadratic, P=0.001) with increasing dosage of Gleptoforte. Overall, there was no difference in performance of pigs receiving the 200mg and 200mg + 100mg injections of Gleptoforte. On d3, prior to the iron injection, there was no difference for any hematological criteria. Both Hgb and Hct had a treatment × day interaction (P=0.001) and increased (quadratic, P=0.001) on d11 and d21 with the highest dosages of Gleptoforte having the greatest Hgb and Hct values compared to lower dosages. On d21, pigs receiving 200mg + 100mg treatment had greater (P>0.05) Hgb and Hct when compared to 200mg. A treatment × day interaction (P=0.001) was observed where Serum Fe increased (linear; P=0.001) on d11 and increased (quadratic; P=0.001) on d21 due to increasing levels of Gleptoforte. On d21 the 200mg + 100mg treatment had greater (P=0.019) Serum Fe compared to 200mg. A treatment × day interaction (P=0.001) for TIBC was observed. On d11 TIBC increased (quadratic, P=0.001) and increased (linear; P=0.001) on d21 with increasing dosages of Gleptoforte. No differences were found in TIBC between 200mg and 200mg + 100mg treatments. In conclusion absence of iron injections resulted in worst blood criteria and growth performance, whereas 100mg of Gleptoforte became the ideal dosage due to greatest growth performance. However, when comparing 200mg to 200mg+100mg growth performance was not affected, although hematological criteria was improved.
Keywords: Fall 2017